2021
DOI: 10.1037/bne0000442
|View full text |Cite
|
Sign up to set email alerts
|

Defining an orbitofrontal compass: Functional and anatomical heterogeneity across anterior–posterior and medial–lateral axes.

Abstract: The orbitofrontal cortex (OFC) plays a critical role in the flexible control of behaviors and has been the focus of increasing research interest. However, there have been a number of controversies around the exact theoretical role of the OFC. One potential source of these issues is the comparison of evidence from different studies, particularly across species, which focus on different specific sub-regions within the OFC. Furthermore, there is emerging evidence that there may be functional diversity across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 105 publications
3
13
0
Order By: Relevance
“…The proposed model of arbitration between learning systems within the rodent lateral OFC is consistent with the proposals that the OFC as a whole is critical for MB learning (Niv, 2019; Wilson et al, 2014). There is emerging evidence that the OFC is comprised of a number of functionally heterogeneous subregions (Barreiros et al, 2021; Bradfield & Hart, 2020; Murray et al, 2015; Panayi & Killcross, 2018; Sallet et al, 2020). One possibility is that the lateral OFC co-ordinates sources of Pavlovian MB and MF information from adjacent OFC subregions via dense intra-OFC reciprocal projections (Barreiros et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model of arbitration between learning systems within the rodent lateral OFC is consistent with the proposals that the OFC as a whole is critical for MB learning (Niv, 2019; Wilson et al, 2014). There is emerging evidence that the OFC is comprised of a number of functionally heterogeneous subregions (Barreiros et al, 2021; Bradfield & Hart, 2020; Murray et al, 2015; Panayi & Killcross, 2018; Sallet et al, 2020). One possibility is that the lateral OFC co-ordinates sources of Pavlovian MB and MF information from adjacent OFC subregions via dense intra-OFC reciprocal projections (Barreiros et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There has been an important focus recently on refining anatomical specificity when exploring medial prefrontal and orbitofrontal cortical function (Barreiros et al, 2021; Coutureau & Killcross, 2003; Killcross & Coutureau, 2003; Laubach et al, 2018). This has been driven by an emerging picture of functional heterogeneity within these cortical subregions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been demonstrated that several nonprincipal nuclei, mainly of the central thalamus, are strongly reciprocally connected with the medial prefrontal cortex (mPFC), and serve a critical role in various affective and cognitive functions (Cassel et al, 2021;Dolleman-van der Weel et al, 2019, Griffin, 2021Kirouac, 2021;McGinty & Otis, 2020;Vertes, Linley, & Hoover, 2015). Unlike, however, well-documented connections of the mPFC with the thalamus (Vertes, 2002(Vertes, , 2004, considerably less attention has been paid to connections of the orbital cortex (ORB) with the thalamus (Hoover & Vertes, 2011;Barreiros, Ishii, et al, 2021)-despite extensive examinations of the behavioral properties of the ORB.…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing suggests that the projections of medial (MO, VO) and lateral (VLO, LO, DLO) regions of the ORB may be distinct, thus supporting very different (or separate) sets of functions for these two regions. Apart from a few previous descriptions of ORB projections (Schilman et al, 2008;Kondo & Witter, 2014;Hoover & Vertes, 2011;Barreiros, Ishii, et al, 2021), the overall projections of the ORB have not been systematically examined in the rat. An analysis of the projections of individual divisions of the ORB would greatly enhance our understanding of the functions of each division-as well as the ORB as a whole.…”
Section: Introductionmentioning
confidence: 99%